THE FIRST EXPERIENCE OF TRANSORAL ROBOT-ASSISTED SURGERY IN A PATIENT WITH OROPHARYNGEAL CANCER (CLINICAL OBSERVATION) - M. A. Kropotov; S. V. Mosin; A. L. Petrova; E. N. Chernikova (Опухоли головы и шеи)
Multiple approaches are currently available for treatment of oropharyngeal cancer. Particular attention is usually paid to preservation of the normal shape of the organ and maintenance of the quality of life in patients. Early-stage oropharyngeal cancer can be treated by both radiotherapy and surgery, including transoral laser microsurgery and robot-assisted surgery.Early diagnosis and the use of modern technological approaches allow to conduct adequate surgical treatment without significant injury of the surrounding soft tissues and bone structures, which in turn promotes both aesthetic and functional rehabilitation of the patient. The case of robot-assisted surgical treatment of the oropharyngeal tumor described in this article is a good example of this rehabilitation.